Inclusion of Different Level Leucaena in Dairy Ration to Balance Rumen Degradable and Undegradable Protein Ratio. Issue 1 (1st April 2022) - Permana, I G; Despal; Rosmalia, A; Rahayu, M D
Abstract: Sustainability use of expensive protein source in a dairy ration requires ration formulation based on rumen degradable and undegradable protein ratio (RDUP). It improves the efficiency of microbial protein synthesis and less feed residue to the environment. Providing less expensive green protein sources such as leucaena (Leucaena leucocephala) is also an alternative. This study aimed to evaluate the effect of dairy ration based on RDUP with leucaena addition on in vitro fermentability and digestibility. This study was conducted in a 4 x 3 factorial randomized block design. Factor 1 was RDUP levels (R1= 60:40; R2= 55:45; R3= 50:50; R4= 45:55) and factor 2 was Leucaena addition (L1= 10%; L2= 20%; L3= 30%). The data were analyzed using ANOVA and followed by the Duncan test. The result showed that increasing RDUP levels increased NH3 concentration and dry matter digestibility. Treatment L2 resulted in a high NH3 concentration compared to other L treatments. The combination of R1 with L2 and L3 resulted in the highest total VFA concentration than other treatments. Protozoa population increased with increasing leucaena in the ration. It is concluded that dairy ration with 60:40 rumen degradable protein to undegradable protein ratio and 20% leucaena can improve ruminal fermentation and digestibility.